Therapeutic modalities in post kala-azar dermal leishmaniasis: A systematic review of the effectiveness and safety of the treatment options - Adrija Datta; Indrashis Podder; Anupam Das; Amrita Sil; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2021)
Post-kala-azar dermal Leishmaniasis (PKDL) is one of the important neglected tropical diseases, which has a tremendous epidemiological significance, being the reservoir of kala-azar. Relapse and resistance to treatment along with the lack of a drug of choice and consensus treatment guideline pose a significant problem in the management of PKDL. The aim of this article was to review the available therapeutic options for PKDL, with special emphasis on their pharmaco-dynamics, pharmaco-kinetics, effectiveness, safety, tolerability, and cost factor. A comprehensive English language literature search was done for therapeutic options in PKDL across multiple databases (PubMed, EMBASE, MEDLINE, and Cochrane) for keywords (alone and in combination). MeSH as well as non-MeSH terms such as "Kala-azar," "Leishmaniasis" AND "Treatment," "Management," "Antimony Sodium Gluconate," "Meglumine Antimoniate," "Amphotericin B," "Paromomycin," "Miltefosine" were taken into consideration. Among 576 relevant articles, 15 were deemed relevant to this review. These articles were evaluated using "Oxford Centre for Evidence-Based Medicine (OCEBM)" AND "strength of recommendation taxonomy" (SORT) with respect to the level of evidence and grade of recommendation. The review includes 15 studies. The use of sodium stibogluconate is being discouraged because of multiple documented reports of treatment failure. Liposomal amphotericin B is emerging as a favorable option, owing to its superiority in terms of effectiveness and safety profile. Miltesfosine is the drug of choice in India because of the ease of oral administration and minimal risk of toxicity. Isolated Paromomycin alone is not effective in PKDL; however, combination therapy with sodium stibogluconate is found to be safe and effective. Combination of amphotericin B and miltefosine is one of the excellent options. Immunotherapy with combination of alum-precipitated autoclaved Leishmania major (Alum/ALM) vaccine + Bacille Calmette-Gu´erin (BCG) has shown promising results. Kala-azar continues to haunt the tropical countries and PKDL being its reservoir is threatening its elimination. With the availability of drugs such as liposomal amphotericin B and miltefosine, apart from the advent of immunotherapy, the future of treatment of this condition looks promising.